Economic Growth in the Warmia and Mazury Voivodship Compared to Selected Countries and Regions of the European Union - Heller, Janusz; Bogdański, Marcin (Olsztyn Economic Journal, 2014)
The aim of the research was to evaluate the level and the dynamics of the economic growth of Warmia and Mazury voivodship compared to the rest of the country and the average economic performance of selected countries and regions of the European Union to determine if the Polish economic gap is decreasing. The obtained results could contribute to the discussion on the efficiency and reasonability of regional policy towards achieving economic cohesion. The analysis indicated that regions of the so-called "eastern wall" of Poland (including Warmia and Mazury voivodship) have a low rate of economic growth. This may suggest that the process of economic divergence has a permanent and objective nature.